The influence of leadership on CMC competences : the moderating role of task interdependence - Scheffler, Isabelle Dominique (2018)
The purpose of this thesis was to study the influence of certain leadership functions on three CMC competences, particularly when the team is highly task interdependent. A survey was conducted and answers were gathered from 106 individuals, who were members of 30 real life teams in total. Results show that the leader’s provision of feedback as well as support of social climate within a team show no influence on any CMC competence whereas the leader’s statement of a team mission shows significant positive influence on CMC knowledge. Additionally, results show that the leader’s encouragement of team self-management has a significant positive influence on all three CMC competences. The model with task interdependence as a moderator was only significant regarding two leadership functions (the provision of feedback and the support of social climate) in connection with one CMC competence, CMC motivation. For both, the moderator only had an influence for lower levels of itself.